Synchronization and Chaos Control Using a Single Controller of Five Dimensional Autonomous Homopolar Disc Dynamo - Lucienne Makouo; Alex Stephane Kemnang Tsafack; Marceline Motchongom Tingue; André Rodrigue Tchamda; Sifeu Takougang Kingni (International Journal of Robotics and Control Systems, 2021)
The electronic implementation, synchronization, and control of hyperchaos in a five-dimensional (5D) autonomous homopolar disc dynamo are investigated in this paper. The hyperchaotic behavior is found numerically using phase portraits and time series in 5D autonomous homopolar disc dynamo is ascertained on Orcad-PSpice software. The synchronization of the unidirectional coupled 5D hyperchaotic system is also studied by using the feedback control method. Finally, hyperchaos found in 5D autonomous homopolar disc dynamo is suppressed thanks to the designed single feedback. Numerical simulations and electronic implementation reveal the effectiveness of the single proposed control.